Determinants of Indonesian Rice Imports - Putra, I Wayan Agus Pratama (CV. Lenggogeni Data Publishing, 2025)
This research analyzes the determinants of rice imports in Indonesia, a critical issue for national food security. The study investigates the influence of rice production, international rice prices, population growth, and per capita expenditure. Utilizing annual secondary data from 2000-2024, the research employs multiple regression analysis. Results indicate that, simultaneously, all four independent variables significantly affect Indonesia's rice imports. Partially, rice production has a negative and significant influence, showing increased domestic output reduces import needs. Population growth impacts positively and significantly, reflecting how expanding population drives demand and pressures domestic supply. Similarly, per capita expenditure on staple grains shows a positive and significant influence, implying heightened purchasing power, if not met by adequate production, increases import requirements. Conversely, international rice prices are found to have no significant influence, suggesting import decisions prioritize urgent domestic needs and price stabilization over global market fluctuations.